3D BASIN MODELLING IN THE CENTRAL PERSIAN GULF, OFFSHORE IRAN. (January 2014) - Mohsenian, E.; Fathi‐Mobarakabad, A.; Sachsenhofer, R. F.; Asadi‐Eskandar, A.
<x xml:space="preserve">Abstract</x> In the Central Persian Gulf, super‐giant natural gas accumulations in Permo‐Triassic reservoirs are assumed to be derived from "hot shale" source rocks in the lower Llandoverian (base‐Silurian) Sarchahan Formation, whereas oil in Mesozoic reservoirs is derived from Mesozoic source rocks. A 3D basin model has been established for a study area located in the Iranian part of the Central Persian Gulf in order to help understand the petroleum systems there. Sensitivity analyses considered different heat flow scenarios, and differences in the timing of Cenozoic uplift and erosion. For the Palaeozoic petroleum system, different thicknesses and distributions of the Silurian source rocks were considered. From current temperature profiles measured in five wells, present‐day heat flow was found to be in the order of 65 mW/m2, while palaeo heat flow was probably between 60 and 68 mW/m2 during Cenozoic maximum burial. For Llandoverian source rocks, oil and gas generation commenced during Jurassic and Late Cretaceous time respectively, and gas generation continued until the Neogene. Sensitivity analyses show that different assumptions on the timing of Cenozoic erosion do not have significant effects on the calculated timing of hydrocarbon generation or on the volume of generated hydrocarbons. As expected however, different heat flow scenarios (e.g. time‐constant heat flow of 65 mW/m2 in the entire study area) had a significant influence. With an assumed 50 m thick Sarchahan "hot shale" succession developed uniformly in the study area (8 % TOC; 470 mg HC / g TOC HI), the model calculated gas accumulations which are of the same order of magnitude as those which have been discovered in this region (e.g. South Pars, Golshan and Balal fields). By contrast, scenarios with thinner "hot shales" and models without the Sarchahan Formation along the Qatar‐South Fars Arch do not predict the known accumulations. These scenarios suggest that prolific Silurian source rocks must be present on both sides of the South Pars / North Dome field, or that lateral gas migration from the south may have supplied the Permo‐Triassic reservoirs. This study shows that the Jurassic (mainly Hanifa / Tuwaiq Mountain Formation) and Cretaceous (Shilaif Formation) source units are not sufficiently mature in the study area to have generated significant volumes of oil. This result supports previous suggestions which envisaged lateral migration from the south of the oil present in Mesozoic reservoirs in the study area.